2020
DOI: 10.13057/biodiv/d211013
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination characteristics in different storage time of Gmelina arborea treated with ultrafine bubbles priming

Abstract: Abstract. Siregar IZ, Muharam KF, Purwanto YA, Sudrajat DJ. 2020. Seed germination characteristics in different storage time of Gmelina arborea treated with ultrafine bubbles priming. Biodiversitas 21: 4558-4564.  Gmelina (Gmelina arborea) seed collected from tropical Indonesian forest experience seed deterioration during storage which is relatively faster than the gmelina seeds originating from temperate regions, such as India and Myanmar. Various treatments have been made to improve the seed viability and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
(17 reference statements)
0
6
0
2
Order By: Relevance
“…Liu et al reported that UFB water exhibited a longer NMR T2 value than that of control water, which resulted in an increase in the mobility of water molecules and a higher germination ratio in barley seeds [13]. The promotion of seed germination due to UFB has also been examined in several aspects: ROS (reactive oxygen species) production in UFB water [14,15]; a change in gene expression within the seed [16]; the number concentration of UFBs [17]; different kinds of gases composing UFBs [18]; and via a comparison between various priming treatments [19].…”
Section: Of 11mentioning
confidence: 99%
“…Liu et al reported that UFB water exhibited a longer NMR T2 value than that of control water, which resulted in an increase in the mobility of water molecules and a higher germination ratio in barley seeds [13]. The promotion of seed germination due to UFB has also been examined in several aspects: ROS (reactive oxygen species) production in UFB water [14,15]; a change in gene expression within the seed [16]; the number concentration of UFBs [17]; different kinds of gases composing UFBs [18]; and via a comparison between various priming treatments [19].…”
Section: Of 11mentioning
confidence: 99%
“…Perlakuan perendaman dengan air UFB terbukti dapat mematahkan dormansi benih saga dalam jangka waktu pendek yakni 12 hari setelah pengecambah dengan nilai perkecambahan di atas 80% (Iswara et al, 2018). Hasil penelitian yang dilakukan pada benih jati putih dengan lama penyimpanan benih yang sudah di atas satu tahun setelah diinvigorasi dengan air UFB viabilitas dan vigornya masih tinggi dengan nilai perkecambahan > 80% dalam jangka waktu 14 hari (Siregar et al, 2020…”
Section: Pendahuluanunclassified
“…Ultra fine bubbles merupakan gelembung berukuran sangat halus dalam air (diameter kurang dari 1 μm) yang mampu merubah sifat fisik dan kimia air (Liu et al, 2013) dan berdampak pada aktifitas molekul air. Penelitian Liu et al (2016) dan Sritontip et al (2019) menunjukkan penggunaan UFB efektif dalam meningkatkan kecepatan berkecambah benih Hordeum vulgare dan Apium graveolens L. Peningkatan juga terjadi pada perkecambahan benih jabon putih (Neolamarckia cadamba) (Fata et al, 2020) dan Gmelina arborea (Siregar et al, 2020).…”
Section: Pendahuluanunclassified